1996
DOI: 10.1002/mds.870110309
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response and R‐R interval variability in multipele system atrophy and idiopathic Parkinson's disease

Abstract: We compared autonomic function in patients with multiple system atrophy (MSA) or with idiopathic Parkinson's disease (IPD) by measuring sympathetic skin response (SSR) and R-R interval variability (RRIV). SSR was investigated in 26 patients (13 with MSA and 13 patients with IPD). RRIV during deep breathing, Valsalva maneuver, and on standing was investigated in 20 patients (nine with MSA and 11 with IPD). MSA and IPD patients had similar age, illness duration, and therapy. Abnormal SSR was more frequent in MSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 17 publications
(6 reference statements)
3
42
1
Order By: Relevance
“…21 Nine of 13 (69.2%) MSA patients had an abnormal SSR compared to only 1/13 (7.7%) PD patients for a sensitivity of 69% and a specificity of 92%. RRIV after deep breathing was abnormal in 8/9 (89%) patients with MSA compared to only 3/11 (27.3%) patients with PD (p ϭ 0.02).…”
Section: Analysis Of the Evidence Question 1: Which Clinical Featurementioning
confidence: 89%
See 1 more Smart Citation
“…21 Nine of 13 (69.2%) MSA patients had an abnormal SSR compared to only 1/13 (7.7%) PD patients for a sensitivity of 69% and a specificity of 92%. RRIV after deep breathing was abnormal in 8/9 (89%) patients with MSA compared to only 3/11 (27.3%) patients with PD (p ϭ 0.02).…”
Section: Analysis Of the Evidence Question 1: Which Clinical Featurementioning
confidence: 89%
“…A variety of noninvasive or minimally invasive procedures have been proposed to distinguish PD from parkinsonian syndromes. Twelve Class III articles [21][22][23][24][25][26][27][28][29][30][31] were identified (table E-3). In these studies, diagnosis of PD or other parkinsonian syndromes were based on clinical criteria.…”
Section: Analysis Of the Evidence Question 1: Which Clinical Featurementioning
confidence: 99%
“…The R-R interval variation (R-R ratio) during the Valsalva manoeuvre has been found statistically significantly different in patients with MSA with respect to those with Parkinson's disease. 10,11 However, evaluation of the R-R ratio in these instances still requires a postural change or a Valsalva manoeuvre that some bradykinetic patients are not able to perform with the degree of competence required to obtain a meaningful result. The technique introduced here permits the study of changes induced in the R-R interval by an acoustic startling stimulus and, therefore, is free from physical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the RRIV correlates with dysautonomia in peripheral neuropathies such as diabetic polyneuropathy and Guillain-Barré syndrome. 18 Considering the peripheral lesions, deformations and contractures which are frequently seen in leprosy patients and create considerable difficulties in SSR studies, the RRIV seems to be a more practical and reliable method for detecting autonomic dysfunction. To our knowledge, there is no RRIV study in patients with leprosy dealing with the parasympathetic function of autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%